TLR-6 SNP P249S is associated with healthy aging in nonsmoking Eastern European Caucasians - A cohort study. Issue 1 (December 2016) - Hamann, Lutz; Bustami, Jasmin; Iakoubov, Leonid; Szwed, Malgorzata; Mossakowska, Malgorzata; Schumann, Ralf; Puzianowska-Kuznicka, Monika
Abstract Background To investigate mechanisms that determine healthy aging is of major interest in the modern world marked by longer life expectancies. In addition to lifestyle and environmental factors genetic factors also play an important role in aging phenotypes. The aged immune system is characterized by a chronic micro-inflammation, known asinflamm-aging, that is suspected to trigger the onset of age-related diseases such as cardiovascular disease, Alzheimer's disease, cancer, and Diabetes Mellitus Type 2 (DMT2). We have recently shown that a Toll-like receptor 6 variant (P249S) is associated with susceptibility to cardiovascular disease and speculated that this variant may also be associated with healthy aging in general by decreasing the process ofinflamm-aging . Results Analyzing the PolSenior cohort we show here that nonsmoking S allele carriers are significantly protected from age-related diseases (P  = 0.008, OR: 0.654). This association depends not only on the association with cardiovascular diseases (P  = 0.018, OR: 0.483) for homozygous S allele carriers, but is also driven by a protection from Diabetes Mellitus type 2 (P  = 0.010, OR: 0.486) for S allele carriers. In addition we detect a trend but no significant association of this allele with inflamm-aging in terms of baseline IL-6 levels. Conclusion We confirm our previous finding of the TLR-6 249S variant to be protective regarding cardiovascular diseases. Furthermore, we present first evidence of TLR-6 249S being involved in DMT2 susceptibility and may be in general associated with healthy aging possibly by reducing the process of inflamm-aging.